Evolutionary divergence of trigeminal nerve somatotopy in amniotes. Issue 6 (20th February 2013) - Rhinn, Muriel; Miyoshi, Kanako; Watanabe, Aki; Kawaguchi, Masahumi; Ito, Fumihiro; Kuratani, Shigeru; Baker, Clare V.H.; Murakami, Yasunori; Rijli, Filippo M.
Abstract The trigeminal circuit relays somatosensory input from the face into the central nervous system. In central nuclei, the spatial arrangement of neurons reproduces the physical distribution of peripheral receptors, thus generating a somatotopic facial map during development. In mice, the ophthalmic, maxillary, and mandibular trigeminal nerve branches maintain a somatotopic segregation and generate spatially organized patterns of connectivity within hindbrain target nuclei. To investigate conservation of somatotopic organization, we compared trigeminal nerve organization in turtle, chick, and mouse embryos. We found that, in the turtle, mandibular and maxillary ganglion neuron rostrocaudal segregation and trigeminal tract somatotopy are similar to mouse. In contrast, chick mandibular ganglion neurons are located rostrally to maxillary neurons, with some intermingling, supporting previous observations (Noden [1980], J Comp Neurol 190:429–444). This organization results in an inversion of the relative positions and less precise axonal sorting of the maxillary and mandibular branches within the trigeminal tract, as compared to mouse and turtle. Moreover, using the turtle and chick orthologs of Drg11 in combination with Hoxa2 expression and axonal tracings from the periphery, we mapped the chick PrV nucleus position to rhombomere 1, confirming previous studies (Marin and Puelles [1995], Eur J Neurosci 7:1714–1738) and in contrast to mouse PrV, which mainly maps to rhombomere 2–3 (Oury et al. [2006], Science 313:1408–1413). Thus, somatotopy of trigeminal ganglion and nerve organization is only partially conserved through amniote evolution, possibly in relation to the modification of facial somatosensory structures and morphologies. J. Comp. Neurol. 1378–1394, 2013. © 2012 Wiley Periodicals, Inc.